Pengaruh Lokasi, Citra Merek, dan Kualitas Produk Terhadap Loyalitas Pelanggan (Studi Kasus Minuman Kekinian di Kota Semarang) - Wahyuningsih, Susanti; Indriyatni, Lies; Widodo, Untung (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2022)
This study aims to examine the effect of location, brand image and product quality on customer loyalty. This study takes the object of Contemporary Drinks in the City of Semarang, with a total population of all consumers of contemporary drink shops in the city of Semarang. The sample taken has a large size and the number is not known with certainty. Therefore, the determination of the sample in this study will be based on Ferdinand (2005) which states that the sample is 5-10 times the number of indicators plus latent variables. Data collection techniques using a questionnaire media. While the technical analysis of the data using multiple regression. The results of the statistical t-test research on the location variable have a significant effect on customer loyalty with a significance level of 0,039 ttable 1,66177, it can be concluded that H1 is accepted. The statistical t-test on the Brand Image variable has a significant effect on Customer Loyalty with a significance level of 0,000ttable 1,66177; it can be concluded that H2 is accepted. The statistical t-test on the Product Quality variable affects customer loyalty with a significance level of 0,000ttable 1,66177; it can be concluded that H3 is accepted. The results of the F statistical test with Fcount of 138,408 with a significance value of 0,000. This can be explained by a significance level below 0,05 and Fcount 138,408 > Ftable 3,10 which means that the variables of Location, Brand Image, and Product Quality together or simultaneously have a significant effect on Customer Loyalty.Keywords: Location; Brand Image; Product Quality; Customer Loyalty